Analisis Kalimat pada Teks Pembelajaran Buku Pendidikan Kewarganegaraan SMA/SMK Kelas XI Kurikulum Merdeka - Ayu Febri Anitasari; Hana Minhatul Maula; Fina Fadhilatul Amalia; Aisyah Mudjahidah; Asep Purwo Yudi Utomo; Nurnaningsih Nurnaningsih (Pusat Riset dan Inovasi Nasional, 2023)
This study analyzes one part of the syntax, i.e. sentences. The method used in this analysis is descriptive qualitative and theoretical syntax. Meanwhile, the study’s data were obtained directly through excerpts of sentences contained in the book “Pendidikan Kewarganegaraan SMA/SMK Kurikulum Merdeka”. The sentence is the largest grammatical unit consisting of a bunch of words, which are arranged by certain rules to explain written language. The main purpose of this research was to find out the types of sentences in the reading text entitled “Tantangan Berpancasila pada Kehidupan Global” which are contained in the book (page 46). Sentences are analyzed in the form of passive sentences, active sentences; transitive sentences, compound sentences; multilevel compound sentences, and single sentences; ekatransitive sentences, adjective sentences. The advantage of this research is that we can find out that the types of sentences that are most often used in this text are compound sentences, while sentences that are rarely found are active and passive